The Influence of Intellectual Capital and Capital Structure on Profitability: Studies of Banking Companies Listed on the IDX in 2016-2019: Pengaruh Intellectual Capital dan Struktur Modal terhadap Profitabilitas: Studi pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2016-2019 - fitri, Fitri Nabila; Arie Cahyani (Economy and Finance Enthusiastic, 2023)
Indonesia's economy in 2022 will grow by 5.31 percent, higher than the achievements in 2021 which will experience a growth of 3.70 percent. One of the sources of economic growth comes from the textile and clothing industry, which is IDR 35.17 trillion in the second quarter of 2022. That number increased by 13.74% compared to last year This study aims to examine the effect of intellectual capital and capital structure on profitability. The population of this study consists of banking companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2019 as the data used in the research. The number of samples in this study were 27 companies selected through purposive sampling. The data analysis tool used in this study was multiple linear regression analysis. The results showed that intellectual capital has a positive effect on profitability, while capital structure has a negative but not significant effect on profitability. The conclusion of this study is that companies can use each of the variables in this study as a strategic tool that can bring benefits to stakeholders, so that investors can consider them when making decisions.